Educational systems matter: differences across European countries in how young people with secondary education experience job insecurity. Issue 7 (17th November 2018) - Ilieva-Trichkova, Petya; Boyadjieva, Pepka
ABSTRACT: This article examines the importance of education in creating differences across European countries with regard to how young people experience job insecurity during their transition from school to work. On a theoretical level, two sets of educational system features which influence job insecurity are identified: institutional (stratification, vocational orientation, standardisation) and structural (expansion of education, development of lifelong learning, education spending). On an empirical basis, data from the Labour Force Survey (2009), the European Social Survey Round 5 (2010/2011), the official statistics, and previous research are analysed. The results show that higher vocational prevalence in secondary education is associated with lower levels of early job insecurity. Our findings contrast previous studies which have not yet revealed any effects of standardising input and output on experiencing qualification mismatches. We found that in countries where the standardisation of the output of educational systems is higher, individuals are less likely to be unemployed. However, the standardisation of input is associated with increased job insecurity. Our analysis also revealed that educational expansion has a negative effect on the likelihood of young people to work part-time jobs and that government expenditure on education is negatively associated with early job insecurity.